RAPID PROTOTYPING FOR THE PRODUCTION OF INTERSTITIAL FREE STEELS - TALAL ABDULLAH (2024)
The miniaturisation of steel production is one of the fronts of metallurgy that must be tackled to provide TATA steel with a competitive edge. This research looks to explore the capabilities of small-scale (40 – 140g) Rapid Alloy Prototyping (RAP) in producing and testing a well-understood Interstitial Free (IF) steel grade, DX57, and comparing it to the industrial product. IF steel is unforgiving towards slight deviations along the entire processing line. To achieve the desired formable properties, the process from casting to annealing must follow a set of strict tolerances. The small-scale RAP attempts to follow most of the industrial processing line; this includes (from start to finish) Coil induction melting, drop casting, reheating, descaling, hot rolling, coiling, sandblasting, cold rolling, and annealing. Techniques such as scanning electron microscope (SEM), optical microscopy, electron backscatter diffraction (EBSD), torsion testing, tensile testing, and optical emission spectroscopy (OES) were used to analyse both the industrial and RAP IF material—the ability to match the tensile-mechanical, thermomechanical, and metallurgical properties of the product demonstrates the merit of the miniaturised processing line. When exploring the scaling effects of miniaturised tensile specimens, representative mechanical properties were achieved; a specimen with a gauge length of 10mm measures an agreeable r-value. Success was seen in the tight compositional control in the synthetic production of IF steel when melting 40g (RAP40g) and 140g (RAP140g) of material in the coil induction drop casting machine and the coil induction centrifugal casting machine, respectively. Detailed analysis of each RAP80g process line stage allowed limitations to be identified and optimised for improved capability.Representative texture and r-values were observed in the RAP80g through process sheet when a single pass 70% hot reduction, 75% cold reduction, and a 100 mpm annealing cycle with a soaking temperature of 820oC was used. A thorough process was explored using a value stream map; with implemented optimisations, 20 alloys can be produced and tested within eight days. Overall, it will assist in establishing a confident campaign towards replacing industrial-scale experimentation of novel steel grade with the RAP process, which is sufficient to explore the matrix of varied parameters to swiftly filter the optimal configuration for upscale.